Testing The Efficiency And Re-evaluating the design on the Removal of Organics With the Usage of Baffled Integrated Suspended Growth System - Shiong, Ernest Ho Zhan (IRC, 2016)
In today’s modern day wastewater treatment system, civilization is provided with a generous amount of options in its disposal or treatment method. However, there is a lack of integrated wastewater reactor systems to which might help in the modernization of the typical wastewater treatment plants. As society moves towards a more integrated approach, so must wastewater treatment systems. The drawbacks in setting up a sewage treatment plant as well as maintaining it comes to light here in this particular project which aims to explore the design feasibility of a new type reactor that may be the first ever of its kind.